THE EFFECT OF ALANG-ALANG (Imperata cylindrica) RHIZOME EXTRACT AS A BIOHERBICIDE FOR CONTROLLING Synedrella nodiflora WEEDS - Nurfadilia Dini Rahayu; Sani Paindra; Maisarah; Claudio Ivan Fahik; Guntoro; Sri Pauja Saragih (Fakultas Pertanian, 2026)
Weeds are one of the major limiting factors in crop production because they compete with cultivated plants for water, light, nutrients, and growing space. Excessive use of chemical herbicides may lead to weed resistance and adverse environmental impacts, highlighting the need for more environmentally friendly weed control alternatives. This study was based on the theory of allelopathy, which explains the ability of allelochemical compounds to inhibit the growth of other plants. The objective of this research was to evaluate the potential of cogongrass rhizome (Imperata cylindrica) extract as a bioherbicide against Synedrella nodiflora. The experiment employed five extract concentrations, namely 0%, 10%, 20%, 30%, and 40%, applied repeatedly through foliar spraying. Data were collected by observing plant height, leaf number, leaf discoloration, and overall visual appearance of the weed. The results showed that increasing extract concentrations led to greater symptoms of chlorosis, necrosis, and wilting. The 40% concentration treatment produced the highest level of weed damage compared to the other treatments. Therefore, cogongrass rhizome extract has the potential to be used as an effective and sustainable natural bioherbicide for controlling Synedrella nodiflora.